Electrocatalytic Hydrogenation of Glucose and Xylose on Electrochemically Roughened Metal Catalysts - Oña Jay Pee; Latonen Rose Marie; Kumar Narendra; Eriksson Jan-Erik; Angervo Ilari; Grénman Henrik (American Chemical Society, 2025)
Electrocatalytic hydrogenation (ECH) of glucose and xylose was studied on Ag, Au, Cu, Pt, and Zn polycrystalline metals. The metal catalysts were roughened electrochemically to expose more active sites. Estimates of surface roughness obtained from the determination of electrochemical surface areas (ECSA) were consistent with those obtained from physical measurements (i.e., confocal white light microscopy). The rough Cu catalyst gave the highest selectivity of 21.1% toward sorbitol production for a glucose conversion of 25.7% and the highest xylitol selectivity of 67.1% for a xylose conversion of 30.8%. Aside from hydrogenation products, significant amounts of 2-deoxyxylitol were formed over the Ag and Zn catalysts during xylose ECH. The results obtained demonstrate the dependence of ECH rate and product selectivity on the chemical properties of the metal catalysts. pH studies of ECH reactions show that appreciable yields of sorbitol and xylitol can be achieved at neutral pH (pH 7), with negligible formation of ketose side products. Furthermore, the Faradaic efficiency (FE) toward xylitol formation increased with more negative applied potentials and was highest at −1.0 V (vs RHE), while the maximum FE for sorbitol occurred at a less negative potential (−0.7 V). Therefore, the ECH rate depends not only on the amount of available chemisorbed hydrogen obtained from water splitting reactions but also on the reactivity of the substrate toward ECH. This work provides the basis for improving electrocatalytic systems for ECH of sugars and a step toward efficient valorization of these compounds from versatile biomass sources.